Proceedings of the 17th ACM International Conference on Supporting Group Work 2012
DOI: 10.1145/2389176.2389216
|View full text |Cite
|
Sign up to set email alerts
|

Discovering habits of effective online support group chatrooms

Abstract: For users of online support groups, prior research has suggested that a positive social environment is a key enabler of coping. Typically, demonstrating such claims about social interaction would be approached through the lens of sentiment analysis. In this work, we argue instead for a multifaceted view of emotional state, which incorporates both a static view of emotion (sentiment) with a dynamic view based on the behaviors present in a text. We codify this dynamic view through data annotations marking inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…For example, analysis of task-relevant differences in information sharing practices between military and civilian pairs performing the same task in a lab study (Mayfield, Garbus, Adamson, & Rosé, 2001; as well as conversational strategies associated with stress reduction in online cancer support chats Mayfield, Wen, Rosé, & Golant, 2012). There we have also found that positioning with respect to knowledge transfer is predictive of stress reduction in these chats; however, it does not appear to be directly related to selfefficacy.…”
Section: Resultsmentioning
confidence: 99%
“…For example, analysis of task-relevant differences in information sharing practices between military and civilian pairs performing the same task in a lab study (Mayfield, Garbus, Adamson, & Rosé, 2001; as well as conversational strategies associated with stress reduction in online cancer support chats Mayfield, Wen, Rosé, & Golant, 2012). There we have also found that positioning with respect to knowledge transfer is predictive of stress reduction in these chats; however, it does not appear to be directly related to selfefficacy.…”
Section: Resultsmentioning
confidence: 99%
“…A major challenge faced when undertaking chat conversations containing unstructured data, is measuring the tone and therefore empathy inclusivity in general in the chat exchanges bearing in mind that in such a situation, there is total lack of body language, which is an important part in emotional interpretation. Moreover, the transition time, that is the interchange time between the chat parties may be too small to make meaningful interpretation and in this way emotional information may not be fully passed on [6].…”
Section: Technology In Counsellingmentioning
confidence: 99%
“…(Ghosh et al, 2017;). Mayfield et al (2012) applied sentimentanalysis combined with extensive turn-level annotation to investigate stress reduction in on-line support group chat-rooms, showing that sentimentanalysis is a good predictor of entrance stress level. Furthermore, similar to our setting, they applied automatic thread-extraction to determine conversation threads.…”
Section: Related Workmentioning
confidence: 99%
“…According to Mayfield et al (2012), users with high incoming stress tend to request less information from others, as a percentage of their time, and share much more information, in absolute terms. In addition, high information sharing has been shown to be a good predictor of stress reduction at the end of the chat (Mayfield et al, 2012). Regarding information sharing, we rely on Dialogue Acts (Austin, 1975) to model the speaker's intention in producing an utterance.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation